Conflicting roles of 20-HETE in hypertension and renal end organ damage - Zhang, Chao (Eur J Pharmacol, 2018)
20-HETE is a cytochrome P450-derived metabolite of arachidonic acid that has both pro- and anti-hypertensive actions that result from modulation of vascular and kidney function. In the vasculature, 20-HETE sensitizes vascular smooth muscle cells to constrictor stimuli and increases myogenic tone. By promoting smooth muscle cell migration and proliferation, as well as by acting on the vascular endothelium to cause endothelial dysfunction, angiotensin converting enzyme (ACE) expression, and inflammation, 20-HETE contributes to adverse vascular remodeling and increased blood pressure. A G protein-coupled receptor was recently identified as the effector for the vascular actions of 20-HETE. In addition, evidence suggests that 20-HETE contributes to hypertension via positive regulation of the renin-angiotensin-aldosterone system, as well as by causing renal fibrosis. On the other hand, 20-HETE exerts anti-hypertensive actions by inhibiting sodium reabsorption by the kidney in both the proximal tubule and thick ascending limb of Henle. This review discusses the pro- and anti-hypertensive roles of 20-HETE in the pathogenesis of hypertension-associated renal disease, the association of gene polymorphisms of cytochrome P450 enzymes with the development of hypertension and renal end organ damage in humans, and 20-HETE related pharmaceutical agents.